Faktor yang Memberikan Impact pada Angka Readmission terhadap Pelaksanaan Discharge Planning Stroke - Renny Triwijayanti; Annisa Rahmania (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the factors that have an impact on readmission rates on the implementation of stroke discharge planning in the ICU and operating room at Muhammadiyah Hospital Palembang. The research method is a quantitative research with an analytical descriptive approach. The results of the study found that knowledge with a p-value of 0.026, and attitudes with a p-value of 0.004. In conclusion, nurses' factors that influence the implementation of discharge planning, namely: knowledge and attitudes. Keywords: Implementation of Patients Going Home, Recurrence of Stroke Patients